Very High Q-Factor Based On G-Shaped Resonator Type Metamaterial Absorber - Al-Badri, Khalid Saeed Lateef (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
High Q-factor based on absorption can be achieved by tuning (the reflection and the transition percentage). In this work, the simple design and simulated in S-band have been investigated. The simulation results of G-shape resonator are shown triple band of absorption peaks 60%, 91.5%, and 70.3%) at resonance frequency 2.7 GHz, 3.26 GHz, and 4.05 GHz respectively. The results exhibited very high of the Q-factor ( 271 ) at resonance frequency ( 3.26 GHz ).  The high Q-factor can be used to enhance the sensor sensing, narrowband band filter and  image sensing.